Bystander stimulation of activated CD4⁺ T cells of unrelated specificity following a booster vaccination with tetanus toxoid - Di Genova, Gianfranco; Savelyeva, Natalia; Suchacki, Amy; Thirdborough, Stephen M; Stevenson, Freda K (European journal of immunology, 2010)
Antigen-specific CD4⁺ T cells are central to natural and vaccine-induced immunity. An ongoing antigen-specific T-cell response can, however, influence surrounding T cells with unrelated antigen specificities. We previously observed this bystander effect in healthy human subjects following recall vaccination with tetanus toxoid (TT). Since this interplay could be important for maintenance of memory, we have moved to a mouse model for further analysis. We investigated whether boosting memory CD4⁺ T cells against TT in vivo would influence injected CD4⁺ TCR transgenic T cells (OT-II) specific for an unrelated OVA peptide. If OT-II cells were pre-activated with OVA peptide in vitro, these cells showed a bystander proliferative response during the ongoing parallel TT-specific response. Bystander proliferation was dependent on boosting of the TT-specific memory response in the recipients, with no effect in naive mice. Bystander stimulation was also proportional to the strength of the TT-specific memory T-cell response. T cells activated in vitro displayed functional receptors for IL-2 and IL-7, suggesting these as potential mediators. This crosstalk between a stimulated CD4⁺ memory T-cell response and CD4⁺ T cells activated by an unrelated antigen could be important in human subjects continually buffeted by environmental antigens.